The dynamics of Indonesian language adaptation in virtual communication among Generation Z using acronyms, abbreviations, and code-mixing - Wirahyuni, Kadek; Putrayasa, Ida Bagus; Paramarta, Ketut; Suandi, Nengah; Rasna, Wayan (Universitas Jambi, Indonesia, 2025)
The primary objectives of this research were to identify the dominant patterns of acronyms and abbreviations, analyze the linguistic and social factors underlying their usage, and evaluate the impact of this phenomenon on the effectiveness, clarity, and communication norms among Generation Z in Bali. The research employed a sequential explanatory mixed-methods design, involving 450 respondents aged 13-28 years. The research findings indicated a high prevalence of acronyms and abbreviations in Gen Z's communication. The ten most dominant acronyms, such as